THE CONTROVERSY ABOUT THE ESSENCE OF LAW: A DISPUTE BETWEEN HART AND DWORKIN - Bello, Petrus CKL (Indonesia Law Review, 2012)
Does the law merely contain rules? Or does it also include morality? The debate between H.L.A. Hart and Ronald Dworkin revolved around this very issue. Hart considered the law is nothing more than a set of rules whereas Dworkin believed that the law contains not only the rules but also principles which are morality and justice. This paper is trying to explore the issue of the relationship of law and morality in the context of this debate between Hart and Dworkin. The debate itself is very significant in the study of law. Following their arguments we can learn a lot about how the law should be understood and practiced. By listening to their whole debate we will also know that Hart’s positivistic thought and Dworkin’s tendency towards the natural law are not mutually negating. Hart Positivism is not anti-morality. It is precisely through positivism which he defended Hart aims at safeguarding the law by morality; whereas Dworkin has shown what had previously forgotten by the legal positivistic way of thinking, that is moral principles are integral parts of the law.